The larvae of the burrowing mayfly genus Tortopus (Ephemeroptera: Polymitarcyidae) - Molineri, Carlos (2007)
The larval stage of Tortopus is redescribed based on three species: T. puella from North America, the only species of the genus previously known from larva, and the larvae of T. obscuripennis and T. sarae from South America described here. Generic characters of the larva include: relatively large finger-like gill near base of maxilla, inner margin of mandibular tusks with a subdistal tubercle, straight or weakly convex frontal ridge present between antennae, reduced unilamellated gill on abdominal segment I. Additionally the male imagines of both Neotropical species are described for the first time, and T. obscuripennis is recorded from Bolivia. Diagnoses, SEM photographs, and illustrations are given for the new stages described and for the identification of the three Tortopus species known as larvae.